Clinical Recommendations of the Russian Gastroenterological Association on Diagnosis and Treatment of Infectious Esophagitis - V. T. Ivashkin; N. D. Yuschuk; I. V. Maev; A. S. Trukhmanov; O. A. Storonova; A. A. Makushina; S. S. Pirogov; O. V. Zayratyants; O. P. Alekseeva; D. N. Andreyev; T. L. Lapina; A. V. Tkachev; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Current clinical recommendations aim to provide gastroenterologists, general practitioners (family doctors), endoscopists and infectionists with modern methods for diagnosis and treatment of infectious esophagitis.Key points. Infectious esophagitis is an esophageal disease of fungal, viral, bacterial or parasitic origin. Esophagus may be affected per se or conjointly in a common gastrointestinal infection. All patients suspected for infectious esophagitis, unless contraindicated, are advised an esophagogastroduodenoscopy with biopsy to confirm diagnosis. Selected incidents of infectious esophagitis require a histological, immunohistochemical examination or polymerase chain reaction-based diagnosis to verify the infectious agent. Uncomplicated infectious esophagitis requires a conservative therapy, mostly on an outpatient basis. However, cases of severe odynophagia, dysphagia, severe pain syndrome, high complication risks (e.g., esophageal ulcer bleeding in thrombocytopenia), severe immunodeficiency, generalised forms of disease and severe concomitant disorders are considered for hospital care. The clinical recommendations outline criteria for the medical care quality assessment and provide relevant information to the patient.Conclusion. Diagnosis of infectious esophagitis capitalises on the clinical picture (odynophagia, dysphagia), presence of immunosuppression, endoscopic and histological evidence. All patients with infectious esophagitis of verified origin are recommended a suitable etiotropic therapy.